2021
DOI: 10.1111/jan.15005
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer‐related lymphoedema: Risk factors and prediction model

Abstract: Aims: To identify the risk factors for lymphoedema following axillary lymph node dissection (ALND) in a European sample and to propose a lymphoedema prediction model for this population. Design: Predictive retrospective cohort study comparing women who developed lymphoedema in 2 years of undergoing ALND with those who did not developed lymphoedema. Methods: We reviewed the clinical records of 504 women who, between January 2008 and May 2018, underwent surgery for breast cancer that involved ALND. Logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
(76 reference statements)
2
23
0
Order By: Relevance
“…Consistent with these results, a 2021 study in a European population found that the only patient-related risk factor for lymphedema following ALND was elevated BMI (Martínez-Jaimez et al, 2022). In light of these findings, our aim here was to achieve an expert consensus regarding weight control strategies for these patients, most of whom will be receiving (or have received) hormone therapy or chemotherapy, both of which can lead to weight gain.…”
Section: Consensus In Roundmentioning
confidence: 64%
“…Consistent with these results, a 2021 study in a European population found that the only patient-related risk factor for lymphedema following ALND was elevated BMI (Martínez-Jaimez et al, 2022). In light of these findings, our aim here was to achieve an expert consensus regarding weight control strategies for these patients, most of whom will be receiving (or have received) hormone therapy or chemotherapy, both of which can lead to weight gain.…”
Section: Consensus In Roundmentioning
confidence: 64%
“…The risk of bias was mainly derived from questions 1, 4, 5, 6, and 8, of which 1 was the sample size, and the researchers believed the number of events per variable (EPV) should be at least 20 [ 45 , 46 ]. And in Liu et al, Kim et al, Wang et al, Penn et al, Basta et al, Byun et al, and Martinez-Jaimez et al [ 13 , 29 , 30 , 32 , 35 , 36 , 39 ], EPV was higher than 20. Question 4 is about participants with missing data handled: most studies did not report changes in follow-up data; only Yuan et al, Liu et al, and Li et al [ 12 , 14 , 30 ] were at a low-bias risk; the study of Yuan et al [ 14 ] has no missing data; and Liu et al and Li et al [ 12 , 30 ] are cross-sectional analysis without missing data.…”
Section: Resultsmentioning
confidence: 91%
“…Question 4 is about participants with missing data handled: most studies did not report changes in follow-up data; only Yuan et al, Liu et al, and Li et al [ 12 , 14 , 30 ] were at a low-bias risk; the study of Yuan et al [ 14 ] has no missing data; and Liu et al and Li et al [ 12 , 30 ] are cross-sectional analysis without missing data. Question 5 is about the selection of predictors, and only Gross et al and Martinez-Jaimez et al [ 11 , 13 ] avoided selecting the predictors with a statistically significant univariable association. Question 8 is about the model performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the survival rates for breast cancer are increasing, cancer survivors face several challenges following cancer treatment including arm lymphedema [ 3 , 4 ]. Arm or secondary lymphedema is characterized by abnormal swelling of one or both arms due to an accumulation of lymph fluid in the interstitial tissue spaces following surgery-associated damage of the lymphatic vessels such as axillary lymph nodes dissection, mastectomy, and regional radiotherapy [ 5 , 6 ]. Due to its multifactorial nature, the pathogenesis of secondary lymphedema remains unclear and the search for molecular factors associated with this condition is still ongoing.…”
Section: Introductionmentioning
confidence: 99%